Monitoring dan Analisis Trafik di Kejaksaan Negeri Jakarta Barat menggunakan Peassler Router Traffic Grapher (PRTG) - Fijatmiko, Bagus; Sopandi, Robi (Jurnal Keilmuan Teknologi Informasi dan Ilmu Manajemen (Justifi), 2022)
This research is intended to analyze and distribute grigrids currently used and network security by providing changes to the design and installing program PRTG (peassler traffic grapher) using the SNMP protocol (simple network management protocol) on west Jakarta's man council. The steps used on this assessment are studies of literature, direct field observations, interviews, and syste tests.. The result is to improve and detract from such agencies as: Failure to check the alignment of how often networks are used, how often they are passed through this network, no recent estimates of how active or frequent users use Internet networks and a lack of daterelated budgets for Internet use and safety, By building a monitoring using the PRG application, it will monitor each user using the network in detail and increase the quality of use for bandwidth in west Jakarta. The conclusion of this study is that west Jakarta's public prosecutor's office building and designing PRG applications can minimize the scope of the problem and can improve performance, efficiency and network security.